Umandawa: Buddhist Transformation in Modern Sri Lanka - De Silva, Gihani (Religions, 2023)
Charismatic Buddhist monks are instrumental in modernising Buddhism as they have been entrusted with an important role of resurrecting religion and Sinhala society throughout the course of Sri Lankan history. Ven. Pitaduwe Siridhamma, later known as Siri Samanthabhadra Arahat Thero, is known as a cosmopolitan modernist monk figure who envisions a modernised form of Buddhism in recent times, which is derived creatively from the discourses and practical ideals in traditional Buddhism. He went further by founding his style initiatives to address Buddhist transformations in modern Sri Lanka. Samanthabhadra revolutionised the monastery space, allowing his supporters to embrace ideals and incorporate them into their everyday life. His project includes a wide range of such activities, expanding opportunities for Buddhist women to pursue their religious vocations, favouring traditional forms of meditation over farming and similar activities. The mission to reform Buddhism in Sri Lanka is not entirely modern, as it also incorporates elements of tradition, as shown in the case study at Umandawa. The modernist ideals and societal demands that define contemporary Buddhism are reflected in the transformation of Buddhism in Sri Lanka.